Studies on Wrightoporia from China 3. Wrightoporia subavellanea sp. nov. based on morphological characters and rDNA sequence data - Chen, Jia-Jia; Cui, Bao-Kai (Phytotaxa, 2014)
Wrightoporia subavellanea sp. nov. is described and illustrated from southern China on the basis of morphological characters and molecular data. It is characterized by an annual growth habit, resupinate basidiocarps with white rhizomorphs, large pores, narrow and strongly dextrinoid skeletal hyphae, broadly ellipsoid to subglobose, thick-walled, finely asperulate and strongly amyloid basidiospores (3.8–4.2 × 2.8–3.2 µm), and presence of gloeoplerous hyphae in trama. A molecular study based the combined ITS (internal transcribed spacer region) and nLSU (the large nuclear ribosomal RNA subunit) dataset supported the position of the new species in Wrightoporia. A key to accepted species of Wrightoporia in China is provided.